Biological characterization of two nemipterus spp. in coastal waters of Bintulu, Sarawak, Malaysia - Tonie, Nettely (2016)
Threadfin bream of the genus Nemipterus is a demersal fish which is one of the valued food fishes in many parts of the world. This species is important economically and trawled in commercial quantities in the South China Sea. The study on Nemipterus in Malaysia especially in Sarawak is little. The present study was to observe the reproductive and feeding biology of Nemipterus japonicus and Nemipterus peronii at coastal area of Bintulu, Sarawak as well as its population dynamic. Monthly sampling was done within a period of 12 months from April 2013 until March 2014 at commercial fish landing site at Bintulu and Kuala Nyalau. Samples in various length sizes was purchased from fisherman and immediately kept in the ice chest and brought back to the laboratory in Department of Animal Science and Fisheries for further analysis. The study of Length Weight Relationship showed that the growth of male and female of both N. japonicus and N. peronii is negative allometric growth. Both of the species tend to become thinner as they grow larger. Natural mortality (M) for N. japonicus was estimated at 1.63 yr-1 and fishing mortality (F) was found to be 1.34 yr-1. The exploitation ratio (E) for N. japonicus is 0.45 which indicates the species is under exploitation of the resource. In case of N. peronii, natural mortality (M) was estimated at 1.74 yr-1 and fishing mortality (F) was 1.79 yr-1. Fishing mortality was higher than natural mortality which indicates that the species has been overfished. The exploitation rate of N. peronii is 0.51 which above the optimum level, it is advisable to maintain and reduce the fishing pressure on the stock. For N. japonicus, the distribution of sexes were significantly in favor of males (χ2 = 12.84; P < 0.05) while for N. peronii, there is no significant different in the distribution of sex ratio. Gonadosomatic Indices (GSI) values of males N. japonicus was ranged from 0.067 to 0.1861 in males and 0.336 to 4.994 in females. N. japonicus in coastal area of Bintulu showed two peaks of spawning season which are in August and March. GSI values of males N. peronii was ranged from 0.0916 to 0.2168 and 0.5828 to 3.2127 in females. In females, spawning season extended within two peaks namely August and March. Based on histological observation, N. japonicus and N. peronii are continuous breeder as the spawning stage observed in all months with the highest percentage in March. For N. japonicus, the mean fecundity was estimated at 40826 while for N. peronii, the mean fecundity was estimated at 44813. The study on stomach fullness between length classes, from small to large size group of N. japonicus found that this species is a moderate feeder to active feeder as it grows. For N. peronii, the species change it feeding habit from poor feeder to active feeder when it reaches the large size. The stomach fullness was varied with season. For N. japonicus, full stomach was observed in all months where the feeding activity was good in April, October and February. In case of N. peronii, the feeding activity was good in April and October. It was decreased furthermore from November to February (wet season) up to the lower percentage. Analyses of prey in the stomachs of N. japonicus and N. peronii identified 18 important items belonging to eight major groups: fish, crustacean, molluscs, echinoderm, foraminifera, polychaete, nematode and unidentified materials. Both occurrence and numerical method showed that crustacean especially crabs were the most preferable food by N. japonicus and N. peronii. This study revealed that N. japonicus and N. peronii are carnivorous and they change their feeding habits from shrimp to crabs and then after fish as it grows.